COMPETENCE APPROACH AS A PRIORITY PEDAGOGICAL PROBLEM - Yu.O. Zenkovych (Academy of Cognitive and Natural Sciences, 2022)
The article deals with formation problem of the value competence under circuinstances of higher school educational establishments. The analysis of the value competence as a notion has been given,